The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations FRESH AIR BUT NO DRAUGHTS Window frames which are ill-fitting should be notified to the Estate Manager. Where they are only slightly too loose, rubber wedges prevent rattling. Tight window frames may be rubbed with good soap to make the sash slide more easily. This also acts as a deterrent to midges, flies, etc. KEEP WOOD IN GOOD CONDITION Defective boards in the floor should be notified to the Estate Manager as soon as they are noticed. Linoleum must not be laid on a solid wooden floor (that is a floor without joists and not ventilated by air bricks in the outside walls) or it will certainly cause dry rot. Do not lay linoleum on a concrete or tiled floor, for mildew would form underneath the linoleum. LEARN A LITTLE FIRST-AID It is useful for a member of the family to know how to deal with simple accidents, and a small first-aid box kept clean and sufficiently stocked, and out of reach of children, is always a useful provision. TAKE CARE OF YOUR ELECTRICAL APPLIANCES See that the flexes of all electrical appliances are in good condition, and are renewed as necessary. A cracked flex is dangerous. Never touch any electrical fittings with wet hands, and if such fittings cannot be kept out of their reach, enforce upon children the rule of keeping their hands off. Electric bulbs need cleaning, but they should never be put into water. Wipe them with a soapy cloth, handling them with great care to avoid jarring the filament, and replace gently without jerking the bulb into its fitting. Electric fires repay attention also. The porcelain finish should be rubbed with a soapy cloth and polished with a soft cloth, while reflectors can be kept bright with a little furniture polish. [illustration] Examining a flex. 19 177/5/8/2